Neoadjuvant endocrine treatment: Precious but insufficiently discovered issue - Oğuz, Arzu; Altundağ, Özden (Acta Medica, 2024)
We would like to emphazise the importance of neoadjuvant endocrine treatment which is overshadowed by neoadjuvant chemotherapy for breast cancer patients. Missing knowledge is evaluation in terms of conventional notion of neoadjuvant chemotherapy that is it better to complete before surgery at least for some selected patients? Another point is, since it is a long term treatment, may be it will be a way give patients the chance to follow up without surgery. So this correspondence tries to ask two questions; shall we think about lengthening the duration of neoadjuvant endocrine treatment in selected patients and who are these patients?